Karakteristik Sosiodemografi Penderita Diabetes Melitus Yang Mengalami Kelainan Periodontal: A Scoping Review - Annisa Nur Diana; Luki Astuti; Lia Hapsari Andayani (Jurnal Kedokteran Gigi Terpadu, 2021)
Background: Diabetes mellitus and periodontal disease are a multifactorial diseases which have a bidirectional relationship. Diabetes mellitus can increase the risk of periodontal diseases while periodontal disease can interfere the glycemic control in diabetic patients by increasing insulin resistance. The epidemiology of both diseases are known to be related by the individuals characteristics of sociodemographic such as gender, age, educational level, socioeconomic and lifestyle. Objective: The aim of this study was to see the sociodemographic characteristics of diabetes mellitus patients with periodontal disease based on gender, age, educational level, socioeconomy, and lifestyle. Method: This type of research is a scoping review using Pubmed and Google Scholar as an electronic databases. Journals with observational study design, such as cross-sectional, case-control, and cohort in English and being published since 2019 were included in the inclusion criteria. Results: 6 journals were obtained according to the inclusion criteria. The increased risk of periodontal disease have a variation in gender, age, and socioeconomic variables. Meanwhile, the variables of educational level and smoking lifestyle showed that there was no variation in the increased risk of periodontal disease. Conclusion: Characteristic of sociodemographic in diabetes mellitus patients suffering periodontal disease have a variations in each variables.